Synthesis and Characterization of Colored Polyureas - M. G. Patel; K. R. Desai; H. S. Patel (E-Journal of Chemistry)
Various disperse dyes based on m-phenylenediamine have been prepared. These dyes then polycondensation with 4,4'-Diphenyl methane diisocyanate. The resultant colored polyureas were characterized by N content, IR spectral studies, Number Average Molecular Weight (Mn) estimation by nonaqueous conductometric titration and thermogravimetry. All the polyureas were subjected to measure electrical conductivity at room temperature.